A Facile Route to Bis(pyridyl‐1, 3, 5‐triazine) Ligands with Fluorescing Properties. Issue 11 (2nd March 2015) - Geist, Matthias F.; Chartrand, Daniel; Cibian, Mihaela; Zieschang, Fabian; Hanan, Garry S.; Kurth, Dirk G.
Abstract: We present a general method for the preparation of bis(pyridyl‐1, 3, 5‐triazine) (dpt) ligands via Stille coupling chemistry. The synthetic procedure surpasses known trimerisation procedures in terms of yield, flexibility, and diversity, as ditopic ligands with different spacers are now available. Polythiophene spacers give rise to different colours by extending the conjugated system and increasing HOMO energy levels. The luminescence properties can be tuned by the spacers, the emission is found in the region from 300–550 nm with nanosecond lifetimes. Preliminary experiments indicate thermochromic properties for the dpt‐Fe II complexes. Abstract : Several bis(pyridyl‐1, 3, 5‐triazine) (dpt) ligands are prepared via Stille coupling with yields and scope of application superior to known trimerisation procedures. Ditopic ligands with different spacers are prepared and incorporation of p ‐ and m ‐substituted phenyl rings enable access to different isomers. The absorption and emission properties can be tuned using oligothiophene spacers.